Serum prohepcidin level in Behcet's disease - Koca, Suleyman Serdar; Ates, Orhan; Ustundag, Bilal; Celiker, Ulkue; Ozgen, Metin; Isik, Ahmet (Ortadogu Ad Pres & Publ Co, 2008)
Objective: The aim of this study was to determine the serum levels oft he prohormone form of hepcidin, prohepcidin, and its relations with iron status, acute phase reactants, cytokines, and its possible role in the development of anemia of chronic disease in patients with Behcet ease (BD). Material and Methods: The study included 37 BID and 28 rheumatoid arthritis (RA) patients and 30 healthy controls (HC). Hematocrit, serum iron status, TNF-alpha, IL-6 and prohepcidin levels were determined. Results:The increases in TNF-alpha level in the BD group and IL-6 level in the RA group were prominent. Serum prohepcidin level in the BD group was lower than the levels in the RA and HC groups (p < 0.01, p > 0.05, respectively). prohepcidin level did not correlate with an), parameters in the BD group, but correlated with hematocrit and ferritin levels in the RA group (r = 0,401, p < 0.05, r = 0.595, p < 0.01 respectively), and TINF-alpha, IL-6 and ferritin levels in the HC group (r = 0.474, p < 0.05, r = 0.526, p < 0.01, r = -0.603, p < 0.01 respectively). Conclusion: Serum prohepcidin concentrations vary widely within the groups as do iron parameters and cytokines. Despite these wide variations the correlations are not significant. The absence of expected correlations indicates that serum prohepcidin is not a useful biomarker for clinical or research purposes.
Keywords: anemia; Behcet syndrome; prohepcidin